Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Please helppp :)
1) Simplify the expression. –2x(1–3x) + (2x + 3)(3x – 2)

Make sure you show all your work for full credit. Use standard polynomial format.


Sagot :

subbhy
I think this is the answer.

Simplified only.
View image subbhy

Answer:

12x² + 3x - 6

Step-by-step explanation: -2x(1-3x) = -2x+6x²

(2x+3)(3x-2), first do 2x

2x × 3x = 6x²

then 2x × -2= -4x

we then move to the number 3

3 × 3x = 9x

3 × -2 = -6

after that we add them together

-2x + 6x² + 6x² - 4x +9x - 6 = 6x² + 6x² is 12x², -2x - 4x + 9x = 3x, and then -6 is by its self

= 12x² + 3x - 6